Impulse Noise on Multi-Antenna Receiving System in WLAN Band - Ahmed, Asif; Qarony, Wayesh; Hossain, M. (Universitas Ahmad Dahlan, 2014)
The effect of impulse noise in wireless communication has been a popular research topic for many researchers over the years. It has been observed that most of the wireless receivers are prone to the disturbing effects of impulsive and nonstationary noise that is generated from different manmade and natural sources. We had constructed a measurement system that acted as a multi-antenna wireless receiver for WLAN band. The measurement has been taken in an impulsive environment with impulse noise sources, such as drill machine, car ignition, etc. The received noise has been approximated by available noise models. The approximation with Gaussian-Gaussian model is presented in this paper. Â